2017
DOI: 10.33549/physiolres.933410
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Uric Acid Levels and Parameters of Metabolic Syndrome

Abstract: Hyperuricemia has been described as associated with the risk of development metabolic syndrome; however the relationship between the uric acid level and particular parameters of metabolic syndrome remained unclear. We performed a cross-sectional study on a cohort of 833 dyslipidemic patients and correlated their levels of uric acid with parameters of insulin resistance, lipid metabolism, C-reactive protein, anthropometric parameters. We also defined patients with hypertriglyceridemic waist phenotype and comper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 23 publications
8
39
0
1
Order By: Relevance
“…At present, the epidemiological studies of dyslipidemia (elevated TG and TC) and HUA have been reported. Some studies showed that elevated UA was associated with high TG, TC, low-density lipoprotein-cholesterol (LDL-C), very low-density lipoprotein-cholesterol (VLDL-C), and low HDL-C, [23][24][25][29][30][31] which did not confirm a causal role for HUA and dyslipidemia. Matsuura et al 32 pointed out that an increase in UA level could be the signal for overfeeding behavior and fat storage in Wistar rats, and then, elevated UA level could act on the urinary bladder mucosa and increases the level of triglyceride and total cholesterol by fructose-induced.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the epidemiological studies of dyslipidemia (elevated TG and TC) and HUA have been reported. Some studies showed that elevated UA was associated with high TG, TC, low-density lipoprotein-cholesterol (LDL-C), very low-density lipoprotein-cholesterol (VLDL-C), and low HDL-C, [23][24][25][29][30][31] which did not confirm a causal role for HUA and dyslipidemia. Matsuura et al 32 pointed out that an increase in UA level could be the signal for overfeeding behavior and fat storage in Wistar rats, and then, elevated UA level could act on the urinary bladder mucosa and increases the level of triglyceride and total cholesterol by fructose-induced.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier cross-sectional study has found that uric acid levels are associated with HDL-c and triglycerides than insulin resistance in dyslipidaemia subjects. Where, atherogenic index of plasma was found to be signi cantly correlated with uric acid [8]. Moreover, Posthoc analysis of GREACE and the life trials changed interest to focus on serum uric acid level and its contribution in atherosclerotic cardiovascular disease [9].…”
Section: Correlated Of Uric Acid With Triglyceridementioning
confidence: 99%
“…In recent years, as a critical mark, systemic measured by SUA has become an essential marker for chronic disease development. Studies have conducted that SUA is associated with various diseases, such as CVDs [22][23][24][25], prehypertension [26][27][28][29], metabolic syndrome [30][31][32], and hypertension [33][34][35]. However, despite the association between SUA level and these risk conditions, SUA level may not be regarded as an independent risk factor.…”
Section: Introductionmentioning
confidence: 99%